(untitled) (MATEMATIKA, 2017)
The control point is the most important element in the production of spline curve or surface model. This is because any changes of control points in the spline model affect the shape of the resulting curve or surface. Wahab and colleagues have introduced fuzzy control points to solve the problem of uncertainty prevailing in the spline modeling. However, based on this concept, this paper will discusses a new type of fuzzy control point that can generates a spline space curve model in 3-dimensional. This is because the generated control point is a 3-dimensional that satisfies the basic concepts of fuzzy set was introduced by Zadeh. However, this paper only taking a B-Spline model as a numerical example in the discussed model.